Peningkatan Keterampilan Menulis Teks Eksposisi melalui Penerapan Strategi Belajar Memutar Pada Siswa Kelas X TKJ-A SMK Negeri 3 Metro Tahun Pelajaran 2017/2018 - Mahlina Gultom (eductum: Jurnal Literasi Pendidikan, 2022)
This study aims to improve the skills of writing expository texts through the application of a circular learning strategy. This research is a CAR research conducted on 34 students of Class X TKJ-A SMK Negeri 3 Metro. The data collection techniques used were exposition text writing tests, field notes, observations, interviews, questionnaires, and photo documentation. Research instruments in the form of student worksheets, field notes, questionnaires, documentation. Data analysis was carried out presented in descriptive qualitative and descriptive quantitative. The results of the study The average score of students' writing exposition text in the pre-action was 56.93, the first cycle was 69.00, and the second cycle was 82.21. The increase in results is also marked by the number of students who have been able to reach the KKM more than 75%. The conclusion of this study is that the skill of writing expository text is improved through the application of the learning strategy of twisting.